Determination of tor tambroides (empurau) growth rate using different feed system - Dollyna, Anak Entri. (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The effect of different type of feeds based on protein and fat level on feed consumption, growth, feed conversion ratio (FCR) and specitic growth rate (SGR) of Tor tambroides (Empurau) was investigated for 13 weeks. The experiment was carried out to determine the suitable level of dietary protein and fat in feed for optimal growth of Tor tambroides. FCR was being used to determine suitable protein dietary level while SGR was used to determine fat dietary level for optimum growth of the fish. There were signi ficant difference (P<O.O I) in feed consumption at different feed types. There were also significant different (P<O.O I) in the final length and final weight of the fish. The higher length increment was observed in fish fed with feed type C (1.49±0.00 cm) and the lowest was feed type B (0.45±O.00 cm). The higher weight increment was tish fed with feed type C (3.23±0.00 g) and the lowest was type B (0.8612±0.00 g). The fish feed with feed type A showed the lowest FCR (4.28, 64.69%) followed by feed type B (5.94, 46.79%) and type C (9.38, 34.81%). Fish fed with feed type C (3.55%) showed the higher value ofSGR while the lowest value was feed type B (0.94%). ANOYA test showed that there were significant difference (P<O.OI) among the different type of feeds. In conclusion, the experiment showed that the optimum level of protein and fat jor the higher growth rate ofthe tish were 32% and 13% respectively.